Trait evaluation of second generation lines of Distichlis spicata - Additon, Tess Katherine, author; Qian, Yaling, advisor; Holm, David, committee member; Barbarick, Ken, committee member (Colorado State University. Libraries, 2014)
Converting to more drought-tolerant, low-input turfgrass varieties that can help conserve water in the landscape is critical for the future of turf in the arid portions of the western United States. This study attempts to address the growing demand for native, low-input turfgrass by breeding a turf-type variety of inland saltgrass (Distichlis spicata) that is well adapted to grow in arid and salty sites while maintaining acceptable quality. Two breeding cycles have been completed for improving the turf quality of inland saltgrass and the current elite lines were selected out of the second-generation nursery to initiate Cycle 3. The goal of this thesis is to evaluate turf-type traits in all second-generation lines. Objectives of this research are three-fold: (1) document, analyze, and report the second-generation nursery of 2,933 saltgrass plots grown at the Horticulture Research Center between 2006-2009, (2) compare improvements of saltgrass through cycles of selections, and (3) maintain and evaluate Cycle 3 crossing blocks for survival, seed yield, and spread. Seed yield increased through cycles of selection and over half the flowering females in the second-generation elite population showed the ability to produce commercially acceptable levels of seed (448-673 kg/ha). Selecting for short canopy height and greater spread/fill was effective and second-generation lines were unique from the wild types and first-generation breeding populations in both of these traits. Nearly 50% of second-generation elite lines showed no signs of leaf rust (Puccinia aristidae) infection in 2008 and roughly 38% showed no signs of leaf shredding and/or browning after mowing. The top 5 elite lines recommended for potential vegetative variety releases from the second-generation were: A37-15x84-6 (M), A37-15xA50-20-1 (F), 84-8x84-6-1B (F), 84-8x84-6-2A (M) and A37-28xA34-18-4B (M). The variability observed in leaf shredding (relating to mowing quality) suggests that more work needs to be done before a uniform, seeded turf-type may be released; however, there is potential to release improved seed for native revegetation projects owing to the increased seed yield and spread in the second-generation lines. Third generation seed was harvested in 2013 and is available for future progeny evaluations.